Effect of cooling temperature on machinability and hole quality in cryogenic drilling of CFRP/Ti stacks - Shunuan Liu; Zhijian Meng; Shiming Liang; Tao Wang; Hao Niu; Bin Luo; Kaifu Zhang (Journal of Materials Research and Technology)
Carbon fiber reinforced polymer/titanium alloy (CFRP/Ti) stacks are extensively employed in modern aircraft owing to their outstanding mechanical properties. At present, cryogenic machining is considered an effective method for reducing drilling-induced defects in CFRP/Ti stacks. However, the effect of cooling temperature on machinability and hole quality of CFRP/Ti stacks remains unclear. To address this issue, a comparative cryogenic drilling experiment under different cooling conditions was performed in this paper. Various drilling performance indicators, such as chip formation, thrust force, hole damage, and dimensional accuracy, were quantified and analyzed. Results demonstrate that cooling temperature significantly affects the drilling process of CFRP/Ti stacks. Specifically, as the cooling temperature drops, Ti chips not only tend to break but also become more irregular, particularly at −50 °C, exacerbating CFRP entrance delamination and hole wall scratches. Additionally, lower cooling temperatures cause the CFRP removal mechanism to shift from bending fracture to brittle fracture, reducing fiber/matrix debonding and fiber pull-out. Compared to drilling at room temperature, the most significant improvement in hole quality is achieved at a cooling temperature of −25 °C, with a maximum reduction of 8.24 % in entrance delamination factor and 46.15 % in cylindricity error. Lower hole damage and better dimensional accuracy can be obtained at this temperature and a feed rate of 0.04 mm/rev. The findings of this study provide guidance for high-performance drilling of CFRP/Ti stacks.